Strategi Engagement China terhadap New Zealand dan Australia Melalui Kerja Sama Bantuan Trilateral di Asia Pasifik - Musfiroh Musfiroh; Hardi Alunaza; Hardi Alunaza (Jurnal Ilmiah Hubungan Internasional, 2020)
China's foreign policy has attracted the attention of many parties. Various views emerged after knowing the spread of Chinese influence, especially in the Asia Pacific Region. Foreign aid is the main tool used by China to approach developing countries. The existence of China indirectly threatens old donor countries that have helped development in developing countries. This article is discussing the involvement of China with old donors such as New Zealand and Australia in trilateral aid cooperation in the Pacific. Trilateral cooperation involves old donor countries, recipient countries, and new donor countries, namely China. This research uses the approach of engagement concept through descriptive research and qualitative approaches with sources of literature study data from books, journals, research reports that support the final results of the analysis. Increasing Chinese aid in the Pacific is seen as a threat to old donor countries in the region. This attitude can indirectly inhibit China in articulating its interests in the Pacific. The results of this paper indicate that China uses engagement strategies through a trilateral assistance cooperation approach to change the behavior and views of old donors on the existence of China in the Pacific. China's role has succeeded in reducing the views and behavior of old donors who consider it as a threat. China also proves the success of exploring broader cooperation with countries in the Pacific.